Wings of Ecstasy: Domenico Bernini’s Vita of St. Joseph of Copertino (1722) by Michael Grosso, translated & edited by Cynthia Clough - Braude, Stephen (Journal of Scientific Exploration, 2018)
This self-published volume is a valuable and natural successor to Grosso’s earlier The Man Who Could Fly: St. Joseph of Copertino and the Mystery of Levitation, which I reviewed very favorably in JSE 30-2 (2016): 275-278. In the earlier work, Grosso presented the amazing essentials of the career of the Flying Friar, including some detailed descriptions from eyewitnesses extracted from contemporary sources (including Bernini). In this book, Grosso performs the additional valuable service of providing an abridged translation of the most important contemporary biography of Joseph, a book brimming with compelling detailed eyewitness accounts, many taken verbatim during Joseph’s protracted inquisition. Details always matter, but perhaps more so in a case so remote from the present day and so extraordinary with respect to the magnitude of the reported phenomena. I remind the reader that the case of St. Joseph provides the earliest outstanding evidence for human levitation and quite possibly the best from any era. The levitations were observed by thousands of people, often near at hand, in flight (not simply at his destination) and in daylight. Moreover, the reports often converge on fascinating and unexpected striking details—e.g., that Joseph’s clothes would not move during his flights, or that he would not extinguish candles as he flew among them. Moreover, Joseph reportedly caused many dramatic healings (again, richly detailed in Bernini’s Vita), and his apparent feats of ESP and bilocation are likewise astounding and difficult to dismiss. So this volume takes us more deeply into the life and character of Joseph and regales us with a great deal more material about the phenomena themselves. In my view, this book is indispensable for students of macro-PK and spontaneous psi generally, and (needless to say) especially so for those who can’t read Bernini in Italian.